2007
DOI: 10.1007/s10682-007-9164-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and contrasting development and reproductive strategies in the pupal hyperparasitoids Lysibia nana and Gelis agilis (Hymenoptera: Ichneumonidae)

Abstract: In most animals, the optimal phenotype is determined by trade-offs in lifehistory traits. Here, I compare development and reproductive strategies in two species of solitary secondary hyperparasitoids, Lysibia nana and Gelis agilis, attacking pre-pupae of their primary parasitoid host, Cotesia glomerata. Parasitoid larvae of both species exploit a given amount of host resources with similar efficiency. However, adults exhibit quite different reproductive strategies. Both species are synovigenic, and female wasp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
110
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(114 citation statements)
references
References 43 publications
4
110
0
Order By: Relevance
“…Several studies have shown that resources obtained from host-feeding may be allocated for both reproduction and/or maintenance (Heimpel and Rosenheim, 1995;Heimpel and Collier, 1996;Giron et al, 2002;Rivero and West, 2005;Kapranas and Luck, 2008;Zhang et al, 2011). Host blood is often important in the production of large, yolky 'anhydropic' eggs (Jervis and Kidd, 1986;Bernstein and Jervis, 2006;Harvey, 2008) that are characteristically produced by many 'idiobiont' ectoparasitoids, i.e. parasitoids that attack non-feeding or non-growing host stages or arrest host development prior to oviposition (Godfray, 1994;Harvey, 2005;Jervis and Ferns, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that resources obtained from host-feeding may be allocated for both reproduction and/or maintenance (Heimpel and Rosenheim, 1995;Heimpel and Collier, 1996;Giron et al, 2002;Rivero and West, 2005;Kapranas and Luck, 2008;Zhang et al, 2011). Host blood is often important in the production of large, yolky 'anhydropic' eggs (Jervis and Kidd, 1986;Bernstein and Jervis, 2006;Harvey, 2008) that are characteristically produced by many 'idiobiont' ectoparasitoids, i.e. parasitoids that attack non-feeding or non-growing host stages or arrest host development prior to oviposition (Godfray, 1994;Harvey, 2005;Jervis and Ferns, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Host blood has also been found to contain certain sugars, such as trehalose and sucrose that are important in reducing the metabolism of lipids (Giron et al, 2002). However, this is certainly not the rule, as the longevity of some parasitoids is not extended at all by host-feeding (Rivero and West, 2005;Harvey, 2008). Host-feeding parasitoids are generally highly synovigenic, meaning that the adult female wasps emerge with few or no ripe eggs and therefore mature most of their eggs after eclosion (Ellers et al, 2000;Jervis et al, 2001Jervis et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations